(untitled) (Journal of Parents and Teachers, 2012)
This editorial presents a number of Padres y Maestros centered on Mathematics, a subject that seems to possess a "curse coefficient" and that obtains low results in the school. It is necessary that all parents and teachers change the way we teach and see Mathematics to improve. They include articles on Mathematics, the Decimal System, teaching experience with a domino, or the keys to school failure.